The Fear of Being Drawn In: Investigating the Ecogothic in the Marysburgh Vortex - Hayes, Matthew (Ontario History)

(untitled) (The Ontario Historical Society, 2025)
The Marysburgh Vortex comprises an area in eastern Lake Ontario said to be home to a malevolent force that has caused many shipwrecks, disappearances, and odd sightings. Drawing on the author’s ethnographic fieldwork and a literary-biographical approach, this article explores the local folklore and published sources for the story, placing it within a longer history of “vortex lore,” which is found primarily in pulp and men’s adventure magazines from the 1960s-1980s. The article argues that descriptions of the Marysburgh Vortex and similar phenomena, such as the Bermuda Triangle, are best read as ecogothic fiction, a genre concerned with repressed guilt and a fear of the natural world. The story of the vortex reveals frustration at the unfulfilled promise of control and domination over nature; a profound alienation that erupts into characterizations of the natural world as evil, grotesque, and unknowable.